2012
DOI: 10.1074/jbc.m112.355420
|View full text |Cite
|
Sign up to set email alerts
|

Sirt-1 Is Required for the Inhibition of Apoptosis and Inflammatory Responses in Human Tenocytes

Abstract: Background: Sirt-1 has been linked to transcriptional silencing and appears to play a key role in inflammation. Results: Transfection of tenocytes with antisense oligonucleotides against Sirt-1-induced inflammation and apoptosis. Conclusion: Sirt-1 can regulate p53 and NF-B activity via deacetylation. Significance: Down-regulation of Sirt-1 by mRNA interference abrogated the effect of resveratrol on p53 and NF-B suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 54 publications
4
56
1
Order By: Relevance
“…Interestingly, MSC derived from SIRT1 knock-out mice showed clearly reduced chondrogenic potential in vitro (67). Indeed, these results are consistent with earlier reports demonstrating that SIRT1 is able to interact with other transcription factors, like Runx2 in osteoblasts or scleraxis in tenocytes (38,62,68) or p53, NF-B, myogenic differentiation, high mobility group I, E2F transcription factor, peroxisome proliferator-activated receptor-␥, and forkhead box O (27,28,30,69).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, MSC derived from SIRT1 knock-out mice showed clearly reduced chondrogenic potential in vitro (67). Indeed, these results are consistent with earlier reports demonstrating that SIRT1 is able to interact with other transcription factors, like Runx2 in osteoblasts or scleraxis in tenocytes (38,62,68) or p53, NF-B, myogenic differentiation, high mobility group I, E2F transcription factor, peroxisome proliferator-activated receptor-␥, and forkhead box O (27,28,30,69).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our laboratory and others have previously reported that resveratrol is an inhibitor of the pro-inflammatory cytokine IL-1␤, highlighting that resveratrol suppressed IL-1␤-induced activation of NF-B and NF-B-dependent gene products (51,57,58). Indeed, we have also shown that resveratrol inhibited IL-1␤-induced apoptosis in tenocytes, and this was linked to changes in the expression of p53, Bax, and caspase-3 (38). However, the mechanisms regulating the suppressive signaling of resveratrol on IL-1␤-induced NF-B transcriptional activity have not yet been fully understood.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…During cyst development, TNF-α is secreted into cyst fluid via an uncertain mechanism, which as a secondary event further stimulates the expression of SIRT1 through TNF-α-mediated NF-κB activation. SIRT1 has been shown to suppress NF-κB activity through deacetylating p65 in different cell lines, which inhibits the inflammation induced by NF-κB (45)(46)(47). Whether there is a feedback loop between SIRT1 expression and NF-κB activation in cystic epithelial cells and whether TNF-α signaling is able to override the inhibition of SIRT1 on NF-κB will require further investigation.…”
Section: Discussionmentioning
confidence: 99%